PENGARUH JUMLAH KREDIT TERHADAP PENDAPATAN PETANI (Studi Pada BUMDes Amanah Desa Berang Rea) - Abdul Rahim; I Ismawati; Ari Apriliansyah (Pusat Riset dan Publikasi, 2020)
This study aims to know the effect of credit amount toward farmers’ income (case study in Village Owned Enterprise (BUMDes) of Amanah Berang Rea village, Moyo Hulu sub-district) in year of 2019. The type of study was associative with quantitative approach. The data in this study were primary and secondary. The data collection techniques used were documentation and interviews. The data analysis technique used was simple linear regression, statistical T test and the coefficient of determination (R2). The results of study showed that the amount of credit had an influence toward the income of farmers in Berang Rea Village, Moyo Hulu sub-district. This was based on the value of t-test with a t-value of 13.610 and a t-table value at a significant level of 5% of 1.992102, so it can be concluded that the t-value was higher than the t-table (13.610>1.992102). The significance value was 0.00<0.005, which means that there was a significant influence between the amount of credit and farmer income. Based on the results of the determination coefficient test (R2), the R2 value was 0.712, which means that the variable ability of the amount of credit in influencing the variation in changes in the amount of farmer income was 71.2%, while the remaining of 28.8% was influenced by other variables.